2018
DOI: 10.1089/neu.2018.5771
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Green Tea Extract Prior to Spinal Cord Injury Prevents Hepatic Iron Overload but Does Not Improve Chronic Hepatic and Spinal Cord Pathology in Rats

Abstract: Spinal cord injury (SCI) disrupts autonomic regulation of visceral organs. As a result, a leading cause of mortality in the SCI population is metabolic dysfunction, and an organ central to metabolic control is the liver. Our recent work showed that rodent SCI promotes Kupffer cell (hepatic macrophage) activation, pro-inflammatory cytokine expression, and liver steatosis. These are symptoms of nonalcoholic steatohepatitis (NASH), the hepatic manifestation of metabolic syndrome, and these pre-clinical data repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 89 publications
(125 reference statements)
0
12
0
1
Order By: Relevance
“…Elevated serum triglycerides were observed at one month after SCI in T3-transected rats associated with increased visceral adiposity (72). In a separate study, serum FFA and glucose were elevated 42 days after a 200 kdyne contusion injury in rats (73). While extensive study of serum lipid profiles has been performed in patients with SCI (1), to date these studies have not characterized serum FFA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum triglycerides were observed at one month after SCI in T3-transected rats associated with increased visceral adiposity (72). In a separate study, serum FFA and glucose were elevated 42 days after a 200 kdyne contusion injury in rats (73). While extensive study of serum lipid profiles has been performed in patients with SCI (1), to date these studies have not characterized serum FFA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic lipids, assessed by Oil red O staining, were also increased at 14 days post injury ( 11 ). A more recent study from the same group found elevated hepatic CD11b at 6-weeks after a 200 kdyne injury at T8 that was associated with increased mRNA levels for several cytokines, including TNFα and IL-1ß, and increased hepatocellular lipids and iron levels ( 73 ). These findings are in agreement with the increased expression of CD11b in liver in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic lipids, assessed by Oil red O staining, were also increased at 14 days post injury (11). A more recent study from the same group found elevated hepatic CD11b at 6-weeks after a 200 kdyne injury at T8 that was associated with increased mRNA levels for several cytokines, including TNFa and IL-1 β, and increased hepatocellular lipids and iron levels (73). These findings are in agreement with the increased expression of CD11b in liver in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Each rat was randomly assigned into three experimental groups: sham-operation group (SH), SCI group, or SCI+HBO group. Meanwhile, the experimental animals were also randomly assigned into four postoperative times (1,3,7, and 14 days). This study did not involve pathogenic microorganisms and was carried out in a general secondary laboratory, and all animals are specific pathogen free.…”
Section: Animalsmentioning
confidence: 99%
“…Apart from the disastrous sensory and motor losses following spinal cord injury (SCI), dysfunction of a variety of organ systems is also widely recognized, such as the gastrointestinal (GI) tract, lung, kidney, spleen, and liver (1,2). GI complications, e.g., barrier dysfunction, motility disorders, and microbial dysbiosis, reprehensively account for 11% of hospitalizations in SCI patients and are regarded as serious problems compromising quality of life (3,4).…”
Section: Introductionmentioning
confidence: 99%